Mother and Her Status in Islam - زيدان, بلسم ابراهيم; قاسم, اسراء ديوان; ساجت, جليلة فياض; اسماعيل, ضياء الدين حمزة (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research showed the role played by the mother in spreading the Sunnah of the Prophet from the beginning of Islam to the third century AH, and what are the problems facing the mother in particular and women in general in spreading the Sunnah. The importance of this research lies in its topic related to the status of the mother in Islam, her role in spreading the purified Prophet's Sunnah and her role in creating a generation that is aware and educated in the correct culture of Islam. The research stressed on showing the tolerance, flexibility and breadth of the Islamic Sharia, the interests of the servants for every time and time. The importance of the research lies in the fact that it gives a picture of the mother inside her home, family and educational institutions in terms of knowing her circumstances and approaching her problems. The research concluded the extent of the importance of the mother in the Islamic community and her effort that she is doing in accordance with the solution of the problems she faces in the community in terms of her dissemination of the Sunnah of the Prophet.